PENERAPAN PRINSIP SYARIAH DALAM PERMODALAN BANK SYARIAH - Wahyu Muhammad, Danang (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Islamic BankÂ is a bankÂ thatÂ is based on Syariah principles. The principles mustÂ always be obeyed bothÂ inÂ the establishment andÂ in the operational,Â includingÂ theÂ financial capital.Â RegardingÂ the capital,Â it must not come fromÂ aÂ sourceÂ thatÂ isÂ consideredÂ asÂ haramÂ accordingÂ toÂ SyariahÂ principles, which willÂ causeÂ a mixÂ between halalÂ andÂ haram.Â SomethingÂ thatÂ isÂ halal mustÂ beÂ strictlyÂ separatedÂ fromÂ somethingÂ thatÂ isÂ haram,Â andÂ vice versa. This paper discusses The Application of Syariah Principles in Islamic Bank Capitalization. Several principles areÂ appliedÂ and mustÂ beÂ obeyed byÂ IslamicÂ Bank,Â namely: Al-TaâawanÂ Principle,Â PrincipleÂ of AvoidingÂ (Al-Ikhtinaz)Â fromÂ gharar, masyir,Â andÂ riba.Â AsÂ aÂ partÂ of IslamicÂ Economy,Â theÂ activitiesÂ ofÂ IslamicÂ BankÂ canÂ be observedÂ fromÂ fourÂ pointsÂ ofÂ view,Â namely;Â ilahiyahÂ economy,Â ahlaqÂ economy, humanityÂ economy,Â and balance economy. Meanwhile, from several viewsnof Muslim Economists,Â it can be concluded that the core of IslamicÂ teachingÂ isÂ tauhid, which meansÂ thatÂ allÂ humanÂ activitiesÂ inÂ the world,Â including economy,Â is merely forÂ ibadahÂ âÂ actÂ ofÂ devotionÂ â whichÂ isÂ aimedÂ atÂ followingÂ oneÂ law,Â AllahâsÂ law.Â TheÂ valueÂ ofÂ tauhid,Â in practice,Â isÂ interpretedÂ in manyÂ valaesÂ andÂ thereÂ areÂ three basicÂ valuesÂ thatÂ become distinguishing factors betweenÂ Islamic economy and other, namely adl, khilafah, and takaful.Â It can be conladed thatÂ is a possibility thatÂ SyariahÂ PrinciplesÂ areÂ violatedÂ byÂ IslamicÂ BankÂ inÂ termsÂ ofÂ itsÂ capitalization.Â ThisÂ can beÂ seeÂ fromÂ the missing of requirements that make it compulsory for all founders to make a statement letter which states that theÂ financialÂ capitalÂ depositedÂ toÂ IslamicÂ BankÂ doesÂ notÂ comeÂ fromÂ aÂ sourceÂ whichÂ isÂ considered asÂ haram accordingÂ to SyariahÂ Principle.Â TheÂ consequenceÂ ofÂ the missing requirementÂ isÂ theÂ possibility ofÂ receiving haramÂ financialÂ capitalÂ from theÂ founders.Â ShouldÂ this happen,Â then Syariah PrincipleÂ is violated.